Group cohesion in the futsal. a theoretical approach (Review) (Revista científica Olimpia, 2020)
This research is related to a topic of great relevance and has the intention of offering some theoretical considerations about group cohesion in the school Futsal. For the realization of this objective a theoretical systematization was carried out based on the review of different sources and the use of theoretical level methods such as: analytical - synthetic, inductive - deductive and document analysis, which allow value judgments to be established. generalizations and positions around the problem that is systematized.
Keywords: group cohesion; psychological clime socio; communication; intervencións psychological.